Demand Analysis of Recreation Visits to Chitral Valley: A Natural Resource Management Perspective (The Pakistan Development Review, 2007)
Recreational visits are primarily about human activity which involves travel from an originating area to a destination for cultural, economic, and social exchange processes. People travel to exotic locations for sight seeing, picnicking, bird watching, and for cultural and religious settings. However, accessibility to such areas is often free, which not only results in environmental hazards but also deprives the cash destitute government from revenue that such these sites offer. Valuing the recreational benefits associated with a destination based on tourists’ preferences can help formulate an appropriate policy for Natural Resource Management (NRM). Environmental and natural resource management studies often try to measure the welfare change associated with a policy change. Welfare is generally defined as area under the demand curve; accordingly, by estimating the demand curve, consumer surplus is obtained which shows the welfare changes associated with an environmental policy change [Gunatilake (2003)]. The recreational values thus obtained can be utilised for a cost benefit analysis of a policy option, thereby, managing a park or a natural resource on a sustainable basis.